2015
DOI: 10.3138/jelis.56.4.283
|View full text |Cite
|
Sign up to set email alerts
|

Competency-based Curriculum: An Effective Approach to Digital Curation Education

Abstract: Texas conducted a project involving rigorous curriculum development and instructional design to address the goal of building capacity in the Library and Information Sciences curriculum. To prepare information professionals with the competencies needed for digital curation and data management practice, the project developed curriculum using a competency-based approach. The purpose of this paper is to discuss the design and implementation of the digital curation curriculum at the University of North Texas. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Third, since certification itself is related to learning results and administrative procedures, it is important to develop substantive curricula, designs, and instructional strategies to build the expected competencies [33,[47][48][49]. The issues at hand include whether to teach competency programs in regular or non-regular subjects, what content to include, and how to implement learner-centered instruction.…”
Section: Discussionmentioning
confidence: 99%
“…Third, since certification itself is related to learning results and administrative procedures, it is important to develop substantive curricula, designs, and instructional strategies to build the expected competencies [33,[47][48][49]. The issues at hand include whether to teach competency programs in regular or non-regular subjects, what content to include, and how to implement learner-centered instruction.…”
Section: Discussionmentioning
confidence: 99%
“…Another example, in which improvisation training could be inserted, is from the University of North Texas. The College of Information at the University of North Texas prepares students with an enhanced competency-based library and information sciences curriculum, with specific emphasis on digital curation (Kim, 2015). A competency-based curriculum seeks to ensure that students can recognize, apply, and execute the knowledge, skills, and abilities currently desired in the library field (Kim, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The College of Information at the University of North Texas prepares students with an enhanced competency-based library and information sciences curriculum, with specific emphasis on digital curation (Kim, 2015). A competency-based curriculum seeks to ensure that students can recognize, apply, and execute the knowledge, skills, and abilities currently desired in the library field (Kim, 2015). As is to be expected, determining an assessment program to measure student acquisition of competencies is difficult, as is keeping a clear focus on field-desired competencies in a rapidly changing job landscape (Saunders, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Nnamani and Ovibe (2015) also confirmed that community-based instruction provided students cross-cultural learning experience. Moreover, Kim (2015) concluded that competency-based curriculum was effective, sustainable and can be customized to address the skill gaps in the rapidly evolving information professions.…”
Section: Discussionmentioning
confidence: 99%